Synthesis of dehydroindolizidine-type poison-frog alkaloids via Michael-type conjugate addition. (1st July 2017) - Zhou, De-Jun; Li, Xue-Yan; Li, Dong; Guo, Zhong-Shuai; Zhang, Qin-Ling; Bie, Hong-Yan; Cui, Zheng-Guo
A concise stereoselective synthesis of proposed dehydroindolizidine-alkaloids of types 179 and 207E1 was accomplished via Michael-type conjugate addition. A comparison of natural 207E and synthesised compound 207E on GC–FTIR revealed the double bond of natural 207E is most likely at the 7, 8-position.